ANALISIS PENILAIAN KUALITAS LAYANAN JASA PENDIDIKAN MENURUT PERSEPSI KEPUASAN MAHASISWA PADA POLITEKNIK AKAMIGAS PALEMBANG - Muhammad Riska; Maulana Effendi (Jurnal Media Wahana Ekonomika, 2014)
The purpose of the research is to find out to analyze perception of student in the Politeknik Akamigas Palembang. In writing this final report, data collected by questioner. Then analyzed using descriptive methods of description, classification and analyze the data and information are relevant to the problems that exist. Then analyze data using SPSS 20,0, and then to determine the consistency or not the service that has been given to the respondent can be seen from the mapping of Cartesian Diagram by comparing the theories are used, then the data obtained in the fact that most respondent at the Politeknik Akamigas Palembang was satisfied with the quality of service provided.  KEYWORD: perception of student, service quality and the mapping of cartesian diagram